The recent industrial policies in Brazil and their conditionalities: a public policy perspective - Machado, João Guilherme Rocha (2022)
My goal with this dissertation is to study industrial policies and conditionalities, using a public policy approach. The intended contribution is to offer insights into the more general literature on industrial policies, usually studied through the economics lens, and to the field of public policies. My research topic is the three recent industrial policies in Brazil. The first is the Industrial, Technological, and Foreign Trade Policy (Política Industrial, Tecnológica e de Comércio Exterior) – PITCE, launched in 2004.The second is the Productive Development Policy (Política de Desenvolvimento Produtivo) – PDP, launched in 2008. The third is the Greater Brazil Plan (Plano Brasil Maior) – PBM, launched in 2011. My research question is “What factors and conditions influenced the formulation and implementation of conditionalities in Brazil’s recent industrial policies between 2003 and 2014?” I carried out qualitative research, relying mainly on a grounded theory method. Data was collected through 26 semi-structured interviews. The first conclusion is that industrial policy is a public policy like any other, and therefore it makes sense to investigate it from a public policy perspective. However, it has often been studied from the perspective of economics. Although economics is one of the building blocks of the field of public policies (in general) and specifically the “public field” in Brazil, and there is certainly dialogue between them, this dialogue is predominantly dominated by economics and relatively one-sided. The second conclusion is that industrial policies can be seen as a public policy comprising a “general guideline” and embedded measures. The nucleus of power responsible for formulating such policies changed considerably across the recent industrial policies, with consequences to their formulation. The third conclusion is that the sensemaking of industrial policies in Brazil is based on narratives and underlying discourses grounded on binary distinctions between the good/moral aspects and the bad/immoral aspects. In this sense, the general narrative is that the recent industrial policies had lower-than-expected results. The underlying discourse is that there is a “right” way to formulate and implement industrial policies, but that was not generally followed in the recent industrial policies leading to results below expectations. Fourthly, putting together industrial policies is both a technical and political process. It is not a rational or sequential endeavor but is permeated by values and influencing and being influenced by other public policies. Fifthly, the importance of conditionalities in industrial policies had a long journey between its emergence in the context of the East Asian experience and its perpetuation as a desired feature of industrial policies in other countries and contexts. The development of the concept of conditionality was related to the successful East Asian experience, its appeal to people with different, and even opposing, worldviews and values, and the fact that the concept “makes sense” in different domains of knowledge and rationales. Finally, I have shown how conditionalities were scattered and present only in a few measures but not as a clear guideline, distinctive feature, or embedded characteristic of any of the recent industrial policies. The lack of conditionalities was connected to an absence of reciprocity and balance between the public and private sectors and a lack of autonomy, power, and capacity of the public sector to include and enforce conditionalities.